Potential futures: land management decision making in the Albertinia-Herbertsdale area of the Gouritz Cluster Biosphere Reserve - Johnson, Ryana Elizabeth Milne (Rhodes University, Faculty of Science, Department of Environmental Science)
Land use change drives biodiversity losses, and UNESCO biosphere reserves serve as laboratories for solving complex problems in the uncertain Anthropocene geological era. Land users' decisions form turning points for land use, biodiversity conservation and future trajectories of land management. This qualitative study used grounded theory, one-on-one interviews and a futures thinking workshop to explore land user decision making in the mixed agricultural Herbertsdale- Albertinia area of the Gouritz Cluster Biosphere Reserve. The study included participants using a variety of land management approaches, ranging from conservation to intensive agriculture. This study found that land managers in the study area interact with multiple complex social-ecological systems, and land management outcomes can be unpredictable for diverse reasons. Informed by learning and risk mitigation as well as their motivation for their present and future, land users are integrating sustainable land management practices in their commercial land management decisions. Their risk adaptation strategies tend to be hands on, independent and practical, as well as action oriented. This can be limiting when adaptation requires abstract, collective or systemic changes. All the participants know that they are dependent on natural resources. They all value their community and social networks. They have a strong appetite for learning, and combine an understanding of the historical context of their land management with an understanding that positive futures will require dynamic and extensive changes at multiple scales. They desire more integrated land use planning at catchment and landscape scales. Collaboration and collaborative strategies emerged as important pathways to the desired future. These include landscape level planning, lobbying for political and legal change, building community, learning, sustainable land management and social integration. It emerged that giving people time to think about abstract or large scale issues is appreciated, and not currently routine. This provides a potential leverage point for collaborative environmental stewardship in this highly biodiverse region.
Keywords: Biosphere reserves -- South Africa; Land management; Decision making; Futures market; Sustainable land management; Adaptation strategy